The competency of Islamic Education Students (IES) during teaching practicum - Ismail, Halim; Othman, Azam; Syed Mahmood, Syarifah Rohaniah; Ibrahim, Hasniza; Ismail, Noor Azizi; Che Noh, Mohd Aderi (Tarbiyah Departement, Sekolah Tinggi Agama Islam (STAI) Muhammadiyah Tulungagung, East Java, Indonesia, 2024)
Malaysia Education Transformation Development Plan (2013-2025) dignified the teaching profession in Malaysia by focusing on programs and activities to strengthen the quality of teaching and learning. Quantitative research design was used to determine the level of students’ competency during school-based teaching practicum. Questionnaires were distributed to 56 former students of Bachelor Islamic Education, ages 21 to 30 years old. The results revealed that competencies in instructional strategies had the highest mean (M=4.19), while competencies in content knowledge had the lowest mean (M=3.93). This study impacted Islamic Education Students (IES) to improve their content knowledge further, identify misunderstandings, scaffold instruction to support students struggling with the learning and materials and incorporate student-led learning into their teaching sessions.